2009
DOI: 10.1159/000267852
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of One-Year Disability and Death in Chinese Hospitalized Women after Ischemic Stroke

Abstract: Background and Purpose: Women have a worse functional outcome after stroke, but the specific factors associated with a poor outcome in women are rarely reported. This study was designed to investigate the clinical predictors of 1-year disability and death in women after ischemic stroke. Methods: Patients with ischemic stroke consecutively registered from March 2002 to July 2007 were followed prospectively for 1 year. Multivariate regression models were employed to analyze predictors of disability (defined as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 64 publications
7
51
1
Order By: Relevance
“…32,33 There were 4 studies specifically designed to identify sex differences in PADL with all finding females had worse functional outcomes after stroke. 9,13,21,22 All studies adjusted for age, 2 adjusted for stroke severity, 21,22 and 2 adjusted for vascular risk factors. 13,21 Among studies not designed to examine sex differences, 5 reported that females had worse outcome than males in unadjusted analyses 10 and independent of age, 11,16,23,24 stroke severity, 23,24 prestroke disability, 23 comorbidities, 24 depression, 11 living alone, 11 recurrent stroke, 11 and cognitive impairments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 There were 4 studies specifically designed to identify sex differences in PADL with all finding females had worse functional outcomes after stroke. 9,13,21,22 All studies adjusted for age, 2 adjusted for stroke severity, 21,22 and 2 adjusted for vascular risk factors. 13,21 Among studies not designed to examine sex differences, 5 reported that females had worse outcome than males in unadjusted analyses 10 and independent of age, 11,16,23,24 stroke severity, 23,24 prestroke disability, 23 comorbidities, 24 depression, 11 living alone, 11 recurrent stroke, 11 and cognitive impairments.…”
Section: Resultsmentioning
confidence: 99%
“…31 Our synthesis of the literature thus suggests that females have worse functional outcomes in the long term after stroke, but the difference between the sexes is greatly reduced when confounding factors are taken into account. Of the 12 studies that adjusted for at least age and stroke severity, 15,17,18,[21][22][23][24][25][26][27]29,30 4 reported that females had worse outcomes than males, whereas the remainder reported no sex difference. Important covariates appeared to be age, stroke severity, and prestroke functional status.…”
Section: Resultsmentioning
confidence: 99%
“…11,[25][26][27] The results of our study concur with studies that found female sex to be predictive of ADL dependency after stroke. [27][28][29][30][31][32][33] In a systematic review by Gall et al, it was hypothesized that women may be more vulnerable than men to worse outcomes because of differences in demographic, social, and medical histories. 34 In the present study, women were ≈4 years older than men and a slightly higher proportion had atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the Chengdu Stroke Registry have been described previously. 10,11 In the present study, we included patients admitted within 1 month after stroke onset from January 2003 to February 2007. Patients who refused to participate in the registry and refused to be followed-up were excluded.…”
Section: November 2012mentioning
confidence: 99%
“…13 Other vascular risk factors surveyed in this study included hypertension, diabetes mellitus, hyperlipidemia, coronary heart disease, previous transient ischemic attacks, history of stroke, and current smoking and alcohol consumption, which have been described in previous reports. 10,11 Stroke severity on admission was measured using the National Institutes of Health Stroke scale (NIHSS). 14 The outcome measures were death, disability, death /disability, and recurrence at 3 months, 6 months, and 1 year after stroke.…”
Section: Definition Of Collected Data and Outcomementioning
confidence: 99%